2019
DOI: 10.1002/cbdv.201900216
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Biological Activities in Limonium Species Collected in Different Biotopes of Tunisia

Abstract: A particular interest is nowadays given to natural antioxidants occurring in foods which can reduce the risk of several diseases through their protective effect. The genus Limonium is widely distributed in different salt regions of Tunisia and known in traditional medicine for the presence of highly effective viral and bacterial replication inhibitors. Limonium leaves have possible beneficial effects on human health for their antioxidant activities and free radical scavenging abilities. To exploit the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
1
17
2
Order By: Relevance
“…Microorganisms such as Escherichia coli or Staphylococcus aureus are responsible for these infectious diseases. A few phytochemical and biological investigations have been performed using extracts of L. oleifolium , specifically obtained from species growing in Tunisia and Italia [24–26] . In addition, these studies revealed the presence of phenolic compounds either as aglycons or glycosides and confirmed exciting bioactivities.…”
Section: Introductionmentioning
confidence: 97%
“…Microorganisms such as Escherichia coli or Staphylococcus aureus are responsible for these infectious diseases. A few phytochemical and biological investigations have been performed using extracts of L. oleifolium , specifically obtained from species growing in Tunisia and Italia [24–26] . In addition, these studies revealed the presence of phenolic compounds either as aglycons or glycosides and confirmed exciting bioactivities.…”
Section: Introductionmentioning
confidence: 97%
“…Phenolic compounds, especially the subgroup of flavonoids, include many secondary metabolites that are potent antioxidants and increase under stressful conditions in many plant species (Di Ferdinando et al 2012). Many Limonium species contain efficient free radical scavengers and have strong antioxidant properties (Senizza et al 2021;Souid et al 2019;Ruiz-Riaguas et al 2020). Field studies on several Limonium species from Tunisia indicated a variation in the levels of polyphenols and flavonoids in relation to seasonal constraints in their natural habitats (Souid et al 2018(Souid et al , 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Many Limonium species contain efficient free radical scavengers and have strong antioxidant properties (Senizza et al 2021;Souid et al 2019;Ruiz-Riaguas et al 2020). Field studies on several Limonium species from Tunisia indicated a variation in the levels of polyphenols and flavonoids in relation to seasonal constraints in their natural habitats (Souid et al 2018(Souid et al , 2019. In salt-treated plants of some species, an increase in the concentration of these compounds has been reported (Wang et al 2016), but in others, only small increases (Souid et al 2016) or no significant variations under water stress (González-Orenga et al 2019a, b) were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular defense strategies developed in plant tolerant species include stress adaptation effectors that mediate ion homeostasis, osmolyte biosynthesis, toxic radical scavenging, water transport and long‐distance response co‐ordination [11] . In addition, enzymatic (catalase, glutathione reductase and several peroxidases) and non‐enzymatic (ascorbate, carotenoids, flavonoids and other phenolics) antioxidant systems are also involved [12,13] . However, the effect of salt stress and plant responses depend on many parameters, including the concentration and time of exposure to salt, plant genotypes and environmental factors [14,15] …”
Section: Introductionmentioning
confidence: 99%